Schubert's Impromptu in G-flat: A Response to Adam Krims - Renwick, William (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2000)
Schubert's Impromptu in G-flat Major is a test case for the varied functions of the upper neighbour. After reviewing Schenker's notion of the upper neighbour, I propose that context is the key to a consistent reading of the upper neighbours in Schubert's Impromptu. The parallelism of neighbours at different levels accounts for much of the organic unity of the composition. Then I reconsider Schoenberg's notion of structural functions, demonstrating the complementary relationship of Schenker and Schoenberg. Finally I revisit the concept of productivity. I argue that most critical approaches employ productivity as a matter of course. The question arises as to which combinations of insight are the most productive.